Effect of Corona Ring Design and Placement on the Distribution of Electric Fields on 500 kV Gantry Substation in Indonesia - Yusrizal Afif; I Made Yulistya Negara; Dimas Anton Asfani (JAREE (Journal on Advanced Research in Electrical Engineering), 2018)
High electric field intensity in string isolators can trigger corona which results in premature aging of the insulator. One solution to overcome this problem is by installing the corona ring, the corona ring will uniform the electric field distribution of the insulator adjacent to the conductor. However, the dimensions and placement of the corona ring will affect the performance of the corona ring in distributing the electric field. therefore, this study will discuss the effect of dimensions and placement of the corona ring on the electric field distribution. Parameters observed were ring length, ring angle and height of corona ring. Simulation with the finite element method (FEM) is used to model the electric field distribution value for each parameter change. As a comparison, changes in corona ring parameters compared to the corona ring design are commonly used in 500 kv gantry substation in Indonesia. Keywords: Corona ring, Electric field distribution, Finite element method (FEM), Insulator string, Porcelain Insulator.